Centro deportivo olmedo rumbo a los 100 años de vida institucional, una retrospección a la historia, mitos, leyendas e identidad comunicacional del club en 2019”. - Evelyn Monserrath, Moya Mariño (2021)
ABSTRACT The research "Susceptibility of Enterococcus faecalis ATCC-29212 against the combination of two natural extracts with calcium hydroxide" had the purpose of analyzing the susceptibility of Enterococcus faecalis with the combination of Zingiber officinale extract and Propolis with calcium hydroxide. Subsequently, the microorganism was inoculated in blood agar and Mueller Hilton Petri dishes with 100µl paper disks of each treatment with the following design: T1 (Calcium hydroxide mixture + 25% Zingiber Officinale extract), T2 (Calcium hydroxide mixture + 75% Zingiber Officinale extract), T3 (Calcium hydroxide mixture + 5% propolis extract) and T4 (Calcium hydroxide mixture + 10% propolis extract). In addition, amoxicillin with clavulanic acid was used as a positive control and distilled water as a negative control, which were incubated at 37ºC for 24 hours. The type of study was quasi-experimental, observational, descriptive, and in vitro, and the instrument was the checklist. The result of the antimicrobial action of the 10% and 5% propolis extract plus calcium hydroxide showed an inhibition halo of 12.78 mm and 8.78 mm, respectively. In addition, the 75% and 25% Zingiber officinale extract in combination showed an inhibitory effect of 13.89 mm and 12.89 mm. It is concluded that there are no statistically significant differences between the inhibitory halos of Zingiber officinale extract at 25% and 75%; however, in combination with propolis extract, it shows greater efficacy at a higher concentration. Keywords: enterococcus faecalis, zingiber officinale propolis, endodontics. Reviewed by: Mgs: Sonia Granizo Lara. ENGLISH PROFESSOR. c.c. 0602088890